Bone-brain interaction: mechanisms and potential intervention strategies of biomaterials - Jiaze Yu; Luli Ji; Yongxian Liu; Xiaogang Wang; Jing Wang; Changsheng Liu (Bone Research)
Abstract Following the discovery of bone as an endocrine organ with systemic influence, bone-brain interaction has emerged as a research hotspot, unveiling complex bidirectional communication between bone and brain. Studies indicate that bone and brain can influence each other’s homeostasis via multiple pathways, yet there is a dearth of systematic reviews in this area. This review comprehensively examines interactions across three key areas: the influence of bone-derived factors on brain function, the effects of brain-related diseases or injuries (BRDI) on bone health, and the concept of skeletal interoception. Additionally, the review discusses innovative approaches in biomaterial design inspired by bone-brain interaction mechanisms, aiming to facilitate bone-brain interactions through materiobiological effects to aid in the treatment of neurodegenerative and bone-related diseases. Notably, the integration of artificial intelligence (AI) in biomaterial design is highlighted, showcasing AI’s role in expediting the formulation of effective and targeted treatment strategies. In conclusion, this review offers vital insights into the mechanisms of bone-brain interaction and suggests advanced approaches to harness these interactions in clinical practice. These insights offer promising avenues for preventing and treating complex diseases impacting the skeleton and brain, underscoring the potential of interdisciplinary approaches in enhancing human health.